Alkaline treatments on EFB fibre: the effect on mechanical-physical properties and fibre-cement hydration rate - Nik Soh, Nik Mohd Zaini; Akasah, Zainal Abidin; Dullah, Hayana; Abdul Aziz, Astimar; Aminudin, Eeydzah (Construction Research Institute Malaysia, 2018)
The natural fibres commonly used to enhance the brittleness of the cement matrix but appropriate fibre should be used for a particular purpose depending upon the type of fibre and characteristics. The Oil Palm Empty Fruit Bunch (EFB) fibre is one of the major crops in Malaysia, which contribute large scale of waste that is durable and make it reasonable for utilization in cement-based product. However, the presence of hemicellulose, lignin and extractive (oil, sugar and starch) affect the performance of EFB fibre and causes an incompatibility of EFB fibre and cement. Hence, this research is been conducted to explore the suitable proportion of Sodium Hydroxide (NaOH) treatment for EFB fibre to increase the compatibility of cement with EFB fibre. The NaOH concentration of 0.2%, 0.4%, 0.6%, 0.8%, 1%, 2%, 3% and 4% were used in this study as a chemical pre-treatment of EFB fibre for surface morphology observation and hydration rate test. Meanwhile for only untreated fibre, fibre treated with 0.4% (low concentration), 1% (medium concentration) and 4% (high concentration) of alkali treatment were tested for tensile strength of single EFB fibre. The fibre treated with NaOH has shown a significant different on the hydration temperature for EFB fibre- cement mixed compared with the untreated fibre. The higher NaOH concentration, the greater hydration temperatures obtain. The Scanning Electron Microscopy (SEM) image show that the increment NaOH concentration applied, the rougher EFB fibre surface is observed with lesser silica body remain. The tensile properties of individual fibre treated with NaOH (0.4%, 1% and 4%) has shown significant increment as compare to the untreated fibre with the highest tensile properties mean value 422.90 N/mm2 at 4% NaOH concentration.